2021
DOI: 10.2147/jmdh.s317896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progressive Resistance Strength Training on Body Mass Index, Quality of Life and Functional Capacity in Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Purpose This study aimed to investigate the effectiveness of progressive resistance strength training of the lower limb rehabilitation protocol (LLRP) on body mass index (BMI), quality of life, and functional capacity in patients with knee osteoarthritis (OA) who were overweight and obese. Patients and Methods Fifty-six patients were allocated into either the Rehabilitation Protocol Group (RPG) or the Control Group (CG) by a computer-generated random number. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…The results of weight loss of the current study are inconsistent with a pragmatic randomized controlled trial that reported that telephone-based weight loss support did not affect weight [34]. A current study concluded that the progressive resistance strength training of LLRP in nonweight bearing positions in patients with knee OA is effective in reducing BMI [35].…”
Section: Discussioncontrasting
confidence: 81%
“…The results of weight loss of the current study are inconsistent with a pragmatic randomized controlled trial that reported that telephone-based weight loss support did not affect weight [34]. A current study concluded that the progressive resistance strength training of LLRP in nonweight bearing positions in patients with knee OA is effective in reducing BMI [35].…”
Section: Discussioncontrasting
confidence: 81%
“…Recently, a study demonstrated that a combination of dietary weight loss and exercise intervention was consistently better in improving a combination of performance and functional outcomes among participants with knee OA compared with exercise alone, diet alone, or a control group (39). In a recent study, a combination of IDC with the strengthening exercises of the major muscle groups of the lower limbs in non-weightbearing positions resulted in improving functional capacity in overweight and obese knee OA patients (38). Similarly, in the current study the intervention in the patients of RGw-mHealth and RGwo-mHealth was also a combination of IDC and progressive LLRP that reported significant results in improving functional capacity.…”
Section: Discussionsupporting
confidence: 61%
“…Because there is no cure for this condition, current medical practice focuses on such interventions that reduce the progression of the disease and the negative impact on healthrelated QoL (37). A recent study concluded that the progressive resistance strength training of LLRP is effective in improving QoL among overweight and obese knee OA patients (38). In the current study, the patients in the RGw-mHealth resulted significantly better QoL compared to both the RGwo-mHealth and CG.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, noninvasive, minimum side effect and cost-effective approaches could be applied in the early or middle stages of knee OA, as they are crucial for relieving symptoms, reducing complications, lowering disability rates, improving health status and lessening the economic burden on the health care system and on patients with knee OA. A recent randomized controlled trial reported improvement in pain and functional capacity by the implementation of strengthening exercises in nonweight-bearing positions in knee OA patients 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%